A study on feasibility of laparoscopic inguinal hernia repair in a District Hospital (Sultan Abdul Halim, Sungai Petani) - Khadir, Norhashimah (2011)

(untitled)
Topic : A study on feasibility of laparoscopic inguinal hernia repair in a district hospital ( Hospital Sultan Abdul Halim, Sungai Petani ). Background: Even though hernia repair is a very common general surgical procedure, repairing bilateral and recurrent inguinal hernia always give problems to the surgeon. The operation performed have higher tendency towards cost increment and morbidity. With the relatively higher capital cost but good outcomes, we decided to study the feasibility of performing laparoscopic inguinal hernia repair in a district hospital setting. Objective: The study objective is to compare the cost effectiveness of laparoscopic versus open inguinal hernia surgery. Besides that, we would like to determine the duration of post operative hospital stay and operative time usage of laparoscopic surgery. In addition, we would like to identify the complications of both operative techniques. Design: Retrospective analysis of laparoscopic and open technique in bilateral and recurrent inguinal hernia. Results: The total numbers of patients were 155. Laparoscopic surgery consisted of 84 patients. 53 cases were bilateral, 19 cases were right recurrent and 12 cases were left recurrent. TEP was performed in 53 cases and 31 cases of TAPP. In open technique, 48 cases were bilateral, 15 cases were right recurrent and 8 were left recurrent. Only 3 female noted and Malay were predominant ( 73 % ). The mean duration of post operative hospital stay was 34 hours in open and 25 hours in laparoscopic surgery (p = 0.002). The mean hospitalization cost of open ( RM 194.50) is cheaper than laparoscopy ( RM 417.35 ). The different was significant as p = < 0.000. The mean operative time is longer in open repair (p = 0.034). The conversion of laparoscopy to open was 6.45 %. Conversion of TEP to TAPP was 4 % only. No major complications noted. Conclusion: It is feasible to perform laparoscopic surgery for recurrent and bilateral inguinal hernia in district or non referral centre. However, well designed study is indicated.